Pembuatan Karbon Aktif dari Ampas Sagu Menggunakan Aktivator ZnCl2 - Rhizal Alfian Abdul Gani; Yohanes David Sokoy; Derlin Lena Samolo; Octolia Togibasa (Jurnal Fisika FLUX, 2021)
Activated carbon is a carbon with an amorphous structure arranged in a parallel hexagonal ring. In this research, activated carbon has been synthesized from sago waste. The purpose of this research was to synthesize activated carbon with ZnCl2 activator and investigate the effect of ZnCl2 activator concentration on the characteristics of activated carbon. Synthesis of activated carbon was carried out with the following stages: dehydration, carbonization, silica extraction with NaOH and ZnCl2 activation with variations in concentrations of 5, 15 and 20%. The characterization of activated carbon was carried out by analyzing the crystal structure and morphology, which was conducted using a scanning electron microscope and x-ray diffractometer. The characterization results showed that the best activated carbon was synthesized from 15% ZnCl2 activator due to its amorphous structure with a relatively small pore size of 2 µm.